Regime Hydraulic Concepts and Equations: The Case of Klang River, Malaysia - Eloubaidy, Aziz F.; Mohammed, Thamer Ahmed; Ghazali, Abdul Halim; Jusoh, Ahmad (Universiti Putra Malaysia Press, 1999)
Updating and testing of available river regime relationships governing the various factors involved in alluvial river design are presented. Analysis of relevant laboratory and field data, gathered from four gauging stations along the water course of Klang River in Malaysia, were undertaken in order to formulate new regime concepts and equations characterizing the river. The functional formulations, to include the slope, rating and flow equations were achieved by employing dimensional analysis techniques relating the geometry and flow parameters